World Internet Development Report 2017 Translated by Peng Ping - Chinese Academy of Cyberspace Studies (Springer Berlin Heidelberg : Imprint: Springer, 2019)
An important outcome of the Fourth World Internet Conference, this book provides a comprehensive account of the status quo and trends in global Internet development. Covering network infrastructure, information technology, digital economy, e-governance, cyber security, and international cyberspace governance, it presents the Global Internet Development Index System to assess the Internet development of various major countries and emerging economies. .